Assessment of severity in patients with acute peritonitis, complicated by abdominal sepsis - Sydorchuk, R. I.; Khomko, O. Y.; Plehutsa, I. M.; Knut, R. P.; Plehutsa, O. M. (Modern medical technology, 2019)
Abdominal sepsis (AS) is one of the most important problems in modern abdominal surgery. Prediction of AS and complications remains a challenge for modern surgery. The aim of the study is to evaluate the prognostic and diagnostic value of clinical and laboratory parameters in order to substantiate the prognostic complex for patients with AS and to improve existing systems for assessing the severity of patients by modification aimed on adapting to the capabilities of clinics. The proposed modification of the severity scoring scale APACHE II, based on the analysis of clinical and laboratory data obtained in 183 patients with acute peritonitis and abdominal sepsis. The complex of physiological parameters and their prognostic significance in AS was determined by in-depth statistical analysis and determination of predicting values. Most of the analyzed indicators had a likely positive prognostic value in the diagnosis and prognosis of AS. At the same time, the predictive value of the qSOFA scale at low values is negligible. Statistically insufficient prognostic value was obtained for increased temperature above 38,0 °C. The data obtained formed the basis for the development of a digital AS and complications prediction system by modifying the APACHE II scale. The proposed patient’ severity scale is accessible and sufficiently informative for use in patients with peritonitis and AS. It is recommended that at least two systems for assessing the severity of a patient’s condition be combined.